A1.2 Fibroblasts Influence Lymphocyte Recruitment and Migration During Resolving and Persistent Arthritis. (25th February 2013) - McGettrick, Helen M; Filer, Andrew; Raza, Karim; Nash, Gerard B; Buckley, Christopher D
Abstract : Background and Objectives: Fibroblasts actively regulate the recruitment of leukocytes by endothelial cells (EC), acting in a pro- or anti-inflammatory manner depending on their site of origin. The phenotype of the fibroblast may be a critical determinant of whether leukocyte recruitment, and therefore inflammation, resolves or persists. Here we examined how synovial fibroblasts from different stages of arthritis influenced the recruitment of peripheral blood lymphocytes (PBL) and their onward migration. Materials and Methods: Fibroblasts were isolated from patients with resolving or persistent arthritis. Rheumatoid arthritis (RA) cohorts were categorised based on the stage of the disease at the time of sample collection: very early; newly presented but established or long established undergoing replacement surgery. Two forms of co-cultures were developed: (1) To assess effects on recruitment, EC and fibroblasts were cultured on opposite sides of porous philtres and incorporated into a novel flow chamber. PBL were perfused and observed as they bind to the EC surface. (2) To examine effects on migration, EC monolayers were formed on a philtre above a collagen gel in which fibroblasts were incorporated. PBL migration through the construct and their location within the gel were assessed. Conditioned media from co-cultures were collected and analysed by Luminex. Results: Fibroblasts from patients with RA increased the ability of EC to support PBL recruitment from flow in a disease duration-specific manner, with binding increasing from very early < established < replacement. However, levels of binding to very early RA co-cultures were similar to those observed when fibroblasts from non-inflamed or resolving tissue were incorporated. In the multi-cellular gel model, all fibroblasts, expected those from non-inflamed tissue, promoted PBL transendothelial migration but had no effect on entry into the gel construct. Interesting, a greater proportion of PBL migrated into the lower half of the gel when fibroblasts from patients with very early and established RA were incorporated. Elevated levels of IL-6, IL-1β, IL-8, Groα and IP-10 were detected in the supernatants from RA co-cultures compared to resolving co-cultures. Resolving fibroblasts dramatically reduced the secretion of these soluble mediators by EC, suggesting they potentially have a suppressive effect. Conclusions: Collectively these initial data indicate that changes in the ability of fibroblasts to influence endothelial and lymphocyte behaviours may occur very early in the development of RA. Moreover, some of these changes are distinct from the phenotype exhibited by fibroblasts taken from non-inflamed tissue and acutely resolving arthritis.